Cadmium and lead affect the status of mineral nutrients in alfalfa grown on a calcareous soil - He, Honghua; Wang, Xia; Wu, Miaomiao; Guo, Lei; Fan, Chenbin; Peng, Qi (Soil science and plant nutrition (Tokyo), 2020)
Cadmium (Cd) and lead (Pb) are toxic trace elements which are not essential for plants but can be easily taken up by roots and accumulated in various organs, and cause irreversible damages to plants. A pot experiment was carried out to investigate the individual and combined effects of Cd (0, 10, 20 mg kg −1 ) and Pb (0, 500, 1000 mg kg −1 ) level in a calcareous soil on the status of mineral nutrients, including K, P, Ca, Mg, S, Fe, Mn, Cu, and Zn, in alfalfa (Medicago sativa L.) plants. Soil Pb level considerably (P ≤ 0.05) affected the concentrations of more elements in plants than soil Cd level did, and there were combined effects of soil Cd level and Pb level on the concentrations of some nutrients (Ca, Mg, and Cu) in plants. The effects of soil Cd level and Pb level on plant nutrient concentrations varied among plant parts. Cd and Pb contamination did not considerably affect the exudation of carboxylates in the rhizosphere. An increase in rhizosphere pH and exudation of significant amounts of carboxylates (especially oxalate) in the rhizosphere might contribute to the exclusion and detoxification of Cd and Pb. Neither shoot dry mass nor root dry mass was significantly influenced by soil Cd level, but both of them were considerably reduced (by up to 25% and 45% on average for shoot dry mass and root dry mass, respectively) by increasing soil Pb level. The interaction between soil Cd level and Pb level was significant for root dry mass, but not significant for shoot dry mass. The results indicate that alfalfa is tolerant to Cd and Pb stress, and it is promising to grow alfalfa for phytostabilization of Cd and Pb on calcareous soils contaminated with Cd and Pb.